Effects of supplementary feeding on interspecific dominance hierarchies in garden birds. - Megan L Francis; Kate E Plummer; Bethany A Lythgoe; Catriona Macallan; Thomas E Currie; Jonathan D Blount (PLoS ONE, 2018)
Individuals often differ in competitive ability, which can lead to the formation of a dominance hierarchy that governs differential access to resources. Previous studies of dominance have predominently focussed on within-species interactions, while the drivers of between-species competitive hierarchies are poorly understood. The increasing prevalence of predictable anthropogenic food subsidies, such as that provided by garden bird feeders, is likely to intensify between-species competition. However, the consequences for resource acquisition await detailed study, and in particular, whether competitive interactions are influenced by food quality is not known. Here, we examine competitive interactions amongst ten passerine species of birds utilising supplementary food sources of differing quality. We show that dominance rank is strongly predicted by body mass across species. Socially dominant, heavier species monopolised access to a food that had a relatively short handling time (sunflower hearts), spent longer on supplementary feeders, and pecked at lower rates. In contrast subordinate, lighter species were constrained to feed on a food that had a relatively long handling time (sunflower seeds with the hull intact). Our findings suggest that differences in body mass may result in between-species dominance hierarchies that place the heaviest species in the greatest control of supplementary feeding sites, gaining superior access to higher value foods. This may have important implications for the use of supplementary feeding as a conservation tool.